Towards factories of the future: migration of industrial legacy automation systems in the cloud computing and Internet-of-things context. Issue 4 (20th April 2020) - Pei Breivold, Hongyu
ABSTRACT: The vision of factories-of-the-future is motivating many industrial companies to modernise their existing portfolio of systems and services to maintain market share and improve business agility. For long-lived industrial systems, it is challenging to adapt legacy assets to a service-oriented stream in cloud computing and Internet-of-things contexts. For this reason, many research studies have proposed techniques and methodologies to migrate legacy industrial functions and systems at different hierarchy levels of automation control. This paper presents an overview of these techniques and methodologies, as well as industry practices to achieve the vision of factories of the future. Better understanding the challenges encountered in legacy migration processes will help researchers and practitioners in their further efforts.